McGrath Video Laryngoscope Versus Macintosh Direct Laryngoscopy for Intubation of Morbidly Obese Patients: A Randomized Trial. (August 2020) - Ruetzler, Kurt; Rivas, Eva; Cohen, Barak; Mosteller, Lauretta; Martin, Adriana; Keebler, Allen; Maheshwari, Kamal; Steckner, Karen; Wang, Mi; Praveen, Chahar; Khanna, Sandeep; Makarova, Natalya; et al.
Abstract : BACKGROUND: Two-thirds of the US population is considered obese and about 8% morbidly obese. Obese patients may present a unique challenge to anesthesia clinicians in airway management. Videolaryngoscopes may provide better airway visualization, which theoretically improves intubation success. However, previous work in morbidly obese patients was limited. We therefore tested the primary hypothesis that the use of McGrath video laryngoscope improves visualization of the vocal cords versus Macintosh direct laryngoscopy (Teleflex, Morrisville, NC) in morbidly obese patients. METHODS: We enrolled 130 surgical patients, aged 18–99 years, with a body mass index ≥40 kg/m 2 and American Society of Anaesthesiologists (ASA) physical status I–III. Patients were randomly allocated 1:1—stratified for patient's body mass index ≥50 kg/m 2 —to McGrath video laryngoscope versus direct laryngoscopy with a Macintosh blade. The study groups were compared on glottis visualization, defined as improved Cormack and Lehane classification, with proportional odds logistic regression model. RESULTS: McGrath video laryngoscope provided significantly better glottis visualization than Macintosh direct laryngoscopy with an estimated odds ratio of 4.6 (95% confidence interval [CI], 2.2–9.8; P < .01). We did not observe any evidence that number of intubation attempts and failed intubations increased or decreased. CONCLUSIONS: McGrath video laryngoscope improves glottis visualization versus Macintosh direct laryngoscopy in morbidly obese patients. Large clinical trials are needed to determine whether improved airway visualization with videolaryngoscopy reduces intubation attempts and failures.